Consistent effects of empagliflozin on cardiovascular and kidney outcomes irrespective of diabetic kidney disease categories: Insights from the EMPA‐REG OUTCOME trial. Issue 12 (10th September 2020) - Wanner, Christoph; Inzucchi, Silvio E.; Zinman, Bernard; Koitka‐Weber, Audrey; Mattheus, Michaela; George, Jyothis T.; von Eynatten, Maximilian; Hauske, Sibylle J.; ,
Abstract: Aim: To explore the cardiovascular (CV) and kidney effects of empagliflozin in patients with different clinical phenotypes of diabetic kidney disease (DKD) (i.e. with the presence or absence of overt albuminuria) participating in the EMPA‐REG OUTCOME trial. Materials and methods: EMPA‐REG OUTCOME randomized participants (1:1:1) to empagliflozin 10 mg, 25 mg or placebo, added to standard of care. Post hoc, patients with different clinical phenotypes of DKD at baseline were categorized in three subgroups: (a) overt DKD (overt albuminuria [urinary albumin‐to‐creatinine ratio of >300 mg/g] with any estimated glomerular filtration rate [eGFR]; n = 769); (b) non‐overt DKD (kidney impairment [eGFR < 60 mL/min/1.73 m 2 ] without overt albuminuria [urinary albumin‐to‐creatinine ratio of ≤300 mg/g]; n = 1290); and (c) 'all others' (eGFR ≥ 60 mL/min/1.73 m 2 without overt albuminuria; n = 4893). Analyses included CV (death, hospitalization for heart failure, all‐cause hospitalization) and selected kidney outcomes, change in eGFR and kidney safety. Cox proportional hazards models assessed the consistency of treatment effect across subgroups. Results: Empagliflozin significantly reduced the risk of CV and kidney outcomes across all subgroups ( P ‐values for interaction >.05), consistent with the overall trial population findings. Empagliflozin also significantly reduced the yearly loss of eGFR, assessed by chronic slopes, in all subgroups. The adverse event profile of empagliflozin was similar across all subgroups. Conclusions: Empagliflozin may improve CV and kidney outcomes and slow the progression of kidney disease in type 2 diabetes patients with DKD, irrespective of its clinical form, both with or without the presence of overt albuminuria.